Incidence of Aleurocanthus spp. (Aleyrodidae: Hemiptera) on betelvine (Piper betle L.) and their interaction with host plants (The Journal of Plant Protection Sciences, 2022)
Betelvine (Piper betle L.) is a perennial evergreen shade loving creeper belonging to the family Piperaceae. In India, it is  commercially cultivated over an area of 50,000 ha as an important and potential cash crop. In spite of the tremendous  potentially of the crop, cultivation of betelvine is highly risky and returns are uncertain because of its susceptibility to  several pests and diseases, aggravated by the nature of the plantation. A good number of hemipteran insect pests occur in  betelvine ecosystem which dwindle betelvine yield potentiality. Among these, the polyphagous betelvine blackfly, Aleurocanthus rugosa Singh (Aleyrodidae: Hemiptera) is a major pest causing severe damage to the foliage in the  conservatories (borojas) of West Bengal. The seasonal incidence of A. rugosa in boroja was recorded during 2003- 2004. A. rugosa adults were active in the boroja through out the year with two peaks, one in pre-monsoon and another in  post-monsoon i.e., period prior initiation of winter season. During the faunastic survey in betelvine, a new species of  Aleurocanthus (description under process) was recorded from West Bengal. This had also been found to occur on Piper  longum L. Another species, A. nubilance (Buckton) which was recorded on betelvine in Bangladesh during 1900, was  not recorded in this area. Detection of host resistance against insect pests is very relevant for genetic improvement  programmes. Till date, scanty information is available on the source of tolerance, if any, against betelvine blackfly. The  reaction of some betelvine cultivars to A. rugosa was evaluated in the boroja with different varietal collections from  different parts of India. None of the entries under the purview was completely free from infestation. A few cultivars  [CARI- 2 (AN), CARI-6(AN) and Bilhari] exhibited moderate resistant reaction against A. rugosa. Awani Pan (Piper  hamiltonii) exhibited resistance against A. rugosa.
Keywords: Betelvine; Piper betle; Aleurocanthus; insect plant interaction